Bullying no ambiente escolar: uma análise a partir das considerações dos professores e alunos de uma escola pública de São Francisco do Pará - GOMES, Daniele Maria Barros (2019)
This research has as its theme Bullying in the school environment: an analysis based on the considerations of teachers and students of a public school in São Francisco do Para. As a General Objective: Analyze from the perspective of teachers and students how and in what way bullying presents itself in the school environment and Specific objectives: Identify how the educational subjects (teachers and students) deal with bullying in the school environment; To verify the pedagogical procedures / practices that teachers and students use about bullying inside the school; Evaluate the view of teachers and students about bullying in school. Methodological theoretical procedures were used as qualitative, bibliographical and field procedures. As final considerations, it is observed that most of the children have seen or suffered bullying, directly or indirectly and that the main culprit of all this is the parents who do not guide, do not limit their children, do not educate, do not talk and good part does not know the friends of the children, from there arises these intolerant and violent people capable of doing any atrocities from the lightest to the most extreme.